Depression and Tobacco Use Among University Students of Chattogram (IAHS Medical Journal, 2026)
Background: University students are at a higher risk of substance use. Depression is associated with a noticeable decline in academic performance and can increase the risk of substance use. This study aimed to find the pattern of depressive symptoms and tobacco use and the association between these two among university students in Chattogram city.Materials and methods: A cross-sectional study was conducted from January 2022 to December 2022 among a convenience sample of 450 university students in four universities of Chattogram City. Past and current pattern of tobacco smoking and use of smokeless tobacco use were measured by self-report. Depressive symptoms were measured by the 9-item Patient Health Questionnaire (PHQ 9) scale. Association between depression and tobacco use was determined by bivariate logistic regression analysis.Results: Out of 450 students, 42 (9.3%) students were smoking tobacco or using smokeless tobacco currently. The depression rate was 64.9% (Respectively, 27.3%, 20%, 10%, and 7.6% had mild, moderate, moderately severe and severe form of depressive symptoms). Logistic regression analysis revealed that current smokers and/or smokeless tobacco users were 2.13 (Odds ratio: 2.13, 95% confidence interval: 1.19-3.18) times more likely to have moderate to severe depression than the students who were not smoking tobacco or using smokeless tobacco currently.Conclusion: The study findings suggest the urgent need to address depression and tobacco use among university students in Chattogram by educating them about mental health, identifying high-risk students and offering easily accessible psychological help.IAHS Medical Journal Vol 8(1), June 2025; 77-82